Meningkatkan Kemampuan Keaksaraan Awal Melalui Bermain Suka-Suka Dengan Media Loose Parts Pada Anak Kelompok B di TK Aisyiyah Bustanul Athfal Slogo - Yuli Astuti, Ratna (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2022)
The early literacy abilities of Group B children in Aisyiyah Bustanul Athfal Slogo Kindergarten have not developed well. This study aims to improve children's early literacy skills through fun playing with loose parts media. This research is a Classroom Action Research. The research subjects were 5 children in Group B. Data collection techniques were carried out using observation and documentation. The tool used is an observation instrument sheet. The data analysis technique was carried out in a quantitative descriptive manner. The success indicator set is that 75% of 5 children have early literacy skills. This research was carried out in two cycles. The results showed that the ability to recognize the early literacy abilities of Group B children at the Pre-action stage was 820%, in Cycle I as much as 50%, and in Cycle II as much as 80%. The percentage gain in Cycle II proves that this research has achieved an indicator of success, namely the child's early literacy ability has increased by 75%. Research steps that can improve early literacy skills are carried out by playing like-like, using real loose parts media and being around the environment. Based on the results of the study, it can be concluded that this activity can improve early literacy skills in Group B at Aisyiyah Kindergarten Bustanul Athfal Slogo.